2023
DOI: 10.1093/geroni/igad079
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Heterogeneity in the Relationship Between Marital Satisfaction and Cognitive Health by Gender and Across the Cognitive Function Distribution

Abstract: Background and Objectives Marital satisfaction has been established as an essential factor for promoting health and well-being in older adults. However, it is unclear whether marital satisfaction is also associated with cognitive health in this population. This study aimed to investigate the longitudinal association between marital satisfaction and cognitive function, while also exploring variations in this relationship by gender and across the cognitive function distribution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Second, the use of cross-sectional data from 2018 to assess social support, depression, and cognitive impairment imposes constraints in deriving causal relationships. While the longitudinal association between marital status and cognitive impairment may vary according to gender and across different levels of cognitive function [ 10 ], other research has indicated cognitive impairment may be related to marital status [ 65 , 66 ], as well as to depression [ 67 ]. Furthermore, depression has been shown to diminish an individual’s social support [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the use of cross-sectional data from 2018 to assess social support, depression, and cognitive impairment imposes constraints in deriving causal relationships. While the longitudinal association between marital status and cognitive impairment may vary according to gender and across different levels of cognitive function [ 10 ], other research has indicated cognitive impairment may be related to marital status [ 65 , 66 ], as well as to depression [ 67 ]. Furthermore, depression has been shown to diminish an individual’s social support [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal qualitative study over 34 years indicated that the frequency of interaction with spouses increased from early adulthood onwards, with emotional closeness deepening throughout adulthood [ 9 ]. Spousal relationships and marital quality are influential in determining psychosocial and cognitive function, especially in older men [ 10 , 11 ]. The enduring nature of marital status represents a potentially important yet often disregarded social factor that either elevates the risk or serves as a protective element against cognitive impairment in the long term [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, our results also indicate that improvements in marital satisfaction can enhance cognitive function, especially among middle‐aged adults. Most extant longitudinal studies examining the influence of marital satisfaction on cognitive function or mental health primarily focus on the detrimental effects of declines in marital satisfaction (J. Kim & Kwon, 2023). Some studies have attempted to measure positive and negative aspects of marital quality separately, using distinct question sets within the same model (Huo et al, 2022; Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this perspective, several studies have investigated the relationship between marital quality and cognitive outcomes (Huo et al, 2022; Liu et al, 2021; Xu et al, 2016). Moreover, recent advancements in quasi‐experimental design have enriched our understanding of this relationship by addressing potential selection biases (J. Kim & Kwon, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation